Investigation of microcirculation in patients with venoarterial extracorporeal membrane oxygenation life support - Yu-Chang Yeh; Chen-Tse Lee; Chih-Hsien Wang; Yu-Kang Tu; Chien-Heng Lai; Yin-Chin Wang; Anne Chao; Chi-Hsiang Huang; Ya-Jung Cheng; Yih-Sharng Chen; on behalf of the NTUH Center of Microcirculation Medical Research (NCMMR) (Critical Care, 2018)
Abstract Background Microcirculatory dysfunction develops in both septic and cardiogenic shock patients, and it is associated with poor prognosis in patients with septic shock. Information on the association between microcirculatory dysfunction and prognosis in cardiogenic shock patients with venoarterial extracorporeal membrane oxygenation (VA-ECMO) support is limited. Methods Sublingual microcirculation images were recorded using an incident dark-field video microscope at the following time points: within 12 h (T1), 24 h (T2), 48 h (T3), 72 h (T4), and 96 h (T5) after VA-ECMO placement. If a patient could be weaned off VA-ECMO, sublingual microcirculation images were recorded before and after VA-ECMO removal. Microcirculatory parameters were compared between 28-day nonsurvivors and survivors with VA-ECMO support. In addition, the microcirculation and clinical parameters were assessed as prognostic tests of 28-day mortality, and patients were divided into three subgroups according to microcirculation parameters for survival analysis. Results Forty-eight patients were enrolled in this study. At T1, the observed heart rate, mean arterial pressure, inotropic score and lactate level of 28-day nonsurvivors and survivors did not differ significantly, but the perfused small vessel density (PSVD) and proportion of perfused vessels (PPV) were lower in the 28-day nonsurvivors than in the survivors. The PSVD and PPV were slightly superior to lactate levels in predicting 28-day mortality (area under curve of 0.68, 0.70, and 0.62, respectively). The subgroup with the lowest PSVD (< 15 mm/mm2) and PPV (< 64%) values exhibited less favorable survival compared with the other two subgroups. Conclusions Early microcirculatory parameters could be used to predict the survival of cardiogenic shock patients with VA-ECMO support. Trial registration ClinicalTrials.gov, NCT02393274. Registered on 19 March 2015.